3D morphological classification of the nasolacrimal duct: Anatomical study for planning treatment of tear drainage obstruction. Issue 4 (1st December 2020) - Lee, Sohyun; Lee, U‐Young; Yang, Suk‐Woo; Lee, Won‐Joon; Kim, Dong‐Ho; Youn, Kwan Hyun; Kim, Yi‐Suk
Abstract: Background: The purpose of this study is to analyze and classify morphological features of the nasolacrimal duct (NLD) through 3D reconstruction to help understand the causes and treatment of NLD obstruction. Methods: In this study, we included 63 males and 55 females who underwent autopsy without NLD obstruction with ages ranging from 20 to 78 years. The NLD was defined from the lacrimal fossa to the opening of the BNLD to the inferior meatus, and all continuous CT images showing the NLD were selected. Segmentation was performed semi‐automatically, and the reconstruction and measurement of NLD was performed using the Mimics program. Results: Overall NLD length, bony nasolacrimal duct (BNLD) length, anteroposterior and transverse diameters at the entrance to the BNLD, anteroposterior and transverse smallest diameters of the BNLD, BNLD volume, and lacrimal sac BNLD angle were significantly higher in males than females ( p  < .05). BNLD direction in the coronal plane was slightly more likely to be inward. The most common type in both sexes was cylinder type (42.0%), males were more likely to have lower‐thicker types (34.1%), and females more likely to have upper‐thicker types (22.7%). Conclusion: There were sex differences in NLD measurements, and females had significantly smaller NLDs. These results may partially explain the increased prevalence of primary acquired NLD obstruction in females. The BNLD tends toward the midline, and inclines posteriorly.